1996
DOI: 10.1099/00207713-46-2-367
|View full text |Cite
|
Sign up to set email alerts
|

Emended Descriptions of Lactobacillus sake (Katagiri, Kitahara, and Fukami) and Lactobacillus curvatus (Abo-Elnaga and Kandler): Numerical Classification Revealed by Protein Figerprinting and Identification Based on Biochemical Patterns and DNA-DNA Hybridizations

Abstract: A former subgenus of the genus Lactobacillus, "Streptobacterium," comprises a wide range of species, including the so-called "atypical streptobacteria," which includes the Lactobacillus sake-Lactobacillus curvatus group. Various identification systems and differentiation criteria for L. sake and L. curvatus have been described previously and are well established. The phenotypic diversity within these two species was the reason for comparing phenotypic variations with DNA homology data. Previously described bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
39
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 37 publications
4
39
1
Order By: Relevance
“…The G+C content of all strains varied around the value 42?5± 0?3 mol%, but strain YMRS3a gave a value of 40?5 mol%. These values are in agreement with the previously described values, generally ranging from 42 to 44 mol% (Hammes & Vogel, 1995 Klein et al (1996). However, the reassociation values obtained for L. curvatus subsp.…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The G+C content of all strains varied around the value 42?5± 0?3 mol%, but strain YMRS3a gave a value of 40?5 mol%. These values are in agreement with the previously described values, generally ranging from 42 to 44 mol% (Hammes & Vogel, 1995 Klein et al (1996). However, the reassociation values obtained for L. curvatus subsp.…”
supporting
confidence: 82%
“…Whereas the former allowed a clear separation between the L. sakei subspecies sakei and carnosus (Fig. 1), confirming data reported by Klein et al (1996), the latter did not (see supplementary material in IJSEM Online).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…curvatus species. However, the studies performed by Klein et al (1996) and Torriani et al (1996) showed different reassociation values and warrant this. More studies must be performed by means of DNA-DNA reassociation with a larger number of strains from this cluster in order to clarify the status of our strains.…”
Section: Discussionmentioning
confidence: 99%